2023
DOI: 10.3390/app13064012
|View full text |Cite
|
Sign up to set email alerts
|

An Advanced Artificial Fish School Algorithm to Update Decision Tree for NLOS Acoustic Localization Signal Identification with the Dual-Receiving Method

Abstract: For indoor sensor systems, it is essential to implement an extra supporting area notification part. To inform the real-time coordinates, the time difference of arrival (TDOA) algorithm can be introduced. For these indoor localization systems, their main processes are often built based on the line of sight (LOS) scenario. However, obstacles make the off-the-shelf localization system unable to play its due role in the flexible non-line of sight (NLOS) scenario. So, it is necessary to adjust the signals according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(19 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…On the one hand, to assist in the mechanism, it turns out to be tremendous to cope with the NLOS transmission path issues. As for the Chirp (Linear Frequency Modulation, LFM) signals in indoor localization systems, it can be clearly found that the Chirp signal used in the system does not bring extra environmental noise and is beneficial for improving the filtering effect due to its significant difference in frequency distribution in the real-world situation [33,34]. As for each acoustic anchor, we consult some conclusions in [33,50].…”
Section: Ensemble Learning Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the one hand, to assist in the mechanism, it turns out to be tremendous to cope with the NLOS transmission path issues. As for the Chirp (Linear Frequency Modulation, LFM) signals in indoor localization systems, it can be clearly found that the Chirp signal used in the system does not bring extra environmental noise and is beneficial for improving the filtering effect due to its significant difference in frequency distribution in the real-world situation [33,34]. As for each acoustic anchor, we consult some conclusions in [33,50].…”
Section: Ensemble Learning Methodsmentioning
confidence: 99%
“…The conversion from coordinates to weights is obtained through the combination of coordinates and radians using geometric principles. The indoor localization system from [33,34,50] can be adopted and it will provide the localization results required for the dual Kinect V2 system. In certain instances, it may be necessary to affix or stabilize some IoT devices [33].…”
Section: Dual Kinect V2 Systemmentioning
confidence: 99%
See 3 more Smart Citations